Analisis Faktor Yang Mempengaruhi Safety Performance dengan Menggunakan Metode Partial Component Regression (PCR) dan Non-Iterative Linear Partial Least Square (Nipals) - Kartika Rahayu Tri Prasetyo Sari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2017)
Safety is a concern of the companies in their business operations. Safety performance is a critical component of health care responsibilities and identify opportunities to improve services. In high-risk organizations, safety performance is generally seen as a leading indicator to provide information about the potential risk dangerous. The purpose of the assesment of safety performance is to identify and manage safety issues. Therefore, this study aimed to analyze the factors that affect the safety performance by PCR and NIPALS method and make the safety performance relational equation model with factors that influence it. The object of the research is a nurse in Bayangkara hospital, Kediri. Research will be conducted a research with quantitative methods. Collection the data for this study using questionnaires distributed to respondents. The required data is data on the variables that have been identified previously. Data needed in the form of metric data with X and Y are more than one. Based on data processing using PCR and NIPALS found that PC Y2 is the best equation model for prediction methods of PCR and Y 3 for NIPALS method. SSE of PCR models smaller than that obtained from NIPALS method, so it can be concluded that the best model is the model equations using PCR. Results obtained Factors affecting safety performance is the security and safety climate leadership. The results were obtained Factors affecting safety performance is the safety climate and safety leadership